Effect of 3 min whole-body and lower limb cold water immersion on subsequent performance of agility, sprint, and intermittent endurance exercise - Zhang, Wei; Ren, Shoupeng; Zheng, Xinyan (Frontiers in Physiology, 2022)
The aim of this study was to investigate the effects of whole-body cold-water immersion (WCWI) and lower-limb cold-water immersion (LCWI) employed during a 15-min recovery period on the subsequent exercise performance as well as to determine the physiological and perceptual parameters in the heat (39℃). Eleven males performed team-sports-specific tests outdoors. The exercise program consisted of two identical exercise protocols (1 and 2) separated by a 15-min recovery period. The participants completed the same tests in each exercise protocol, in the following order: agility T test (T-test), 20-m sprint test (20M-ST), and Yo-Yo Intermittent Endurance Test Level 1 (Yo-Yo). During the recovery period, a 3-min recovery intervention of a passively seated rest (control, CON), WCWI, or LCWI was performed. The T-test and 20M-ST for the CON group were significantly longer during exercise protocol 2, but they were not significantly different between the two exercise protocols for the WCWI and LCWI groups. The completed Yo-Yo distance for the CON and LCWI groups was shorter during exercise protocol 2, but it was not significantly different between the two exercise protocols for the WCWI group. The chest temperature (Tchest), upper arm temperature (Tarm), thigh temperature (Tthigh), mean skin temperature (Tskin), and thermal sensation (TS) values were lower for the WCWI group than for the CON group; but only the Tthigh, Tskin, and TS values were lower for the LCWI group compared to the CON group. The Tchest, Tarm, Tskin, and TS values after the intervention were lower for the WCWI group than for the LCWI group. None of the three intervention conditions affected the core temperature (Tcore), heart rate (HR), or rating of perceived exertion (RPE). These results suggest that WCWI at 15 ℃ for 3 min during the 15-min recovery period attenuates the impairment of agility, sprint, and intermittent-endurance performance during exercise protocol 2, but LCWI only ameliorates the reduction of agility and sprint performance. Furthermore, the ergogenic effects of WCWI and LCWI in the heat are due, at least in part, to a decrease of the Tskin and improvement of perceived strain.